2006
DOI: 10.1191/0269216306pm1149oa
|View full text |Cite
|
Sign up to set email alerts
|

Factors predictive of preferred place of death in the general population of South Australia

Abstract: In a population survey, 2652 respondents aged 15+ years reported their preferred place of death, if dying of 'a terminal illness such as cancer or emphysema', to be home (70%), a hospital (19%), hospice (10%), or nursing home (<1%). The majority of respondents in all socio-demographic categories reported a preference for dying at home, with the greatest majorities occurring in younger age groups. After weighting to the age-sex distribution of all South Australian cancer deaths, 58% in our survey declared a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
159
4
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(182 citation statements)
references
References 23 publications
14
159
4
5
Order By: Relevance
“…These concerns have also been reported by other patient groups. 12,21 Although there is conflicting evidence about the quality of care received in inpatient settings versus at home, 2 some patients perceive that having access to professional medical care in inpatient settings is essential. People may also feel a sense of security from receiving care at a hospital with which they are already familiar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns have also been reported by other patient groups. 12,21 Although there is conflicting evidence about the quality of care received in inpatient settings versus at home, 2 some patients perceive that having access to professional medical care in inpatient settings is essential. People may also feel a sense of security from receiving care at a hospital with which they are already familiar.…”
Section: Discussionmentioning
confidence: 99%
“…2 In one US study of terminally ill patients with cancer, perceived quality of life, the availability and capacity of family carers, the impact their choice would have on others, and quality of healthcare were major considerations in preference. 12 Greater understanding of patient choices and the underlying reasons for these choices can help inform the development of more effective, patientcentered care models that may be more widely available and integrated across care settings. 2 To do this, patients must be given opportunities to articulate and implement their choice through proper discussions with key individuals, including healthcare providers and support persons.…”
mentioning
confidence: 99%
“…A populationbased survey in Australia determined factors associated with preferred death place, with 2657 respondents asked to imagine they were dying of a terminal illness. 17 This study revealed 70% wanted at the time of death to be at home, 19% in hospital, 10% in a hospice, and 1% in a nursing home. 17 Six factors predicted a home death preference: younger age, male, born in Ireland/UK or Italy/Greece, better physical health, poorer mental health, and having few concerns about home deaths.…”
Section: Literature Reviewmentioning
confidence: 99%
“…17 This study revealed 70% wanted at the time of death to be at home, 19% in hospital, 10% in a hospice, and 1% in a nursing home. 17 Six factors predicted a home death preference: younger age, male, born in Ireland/UK or Italy/Greece, better physical health, poorer mental health, and having few concerns about home deaths. 17 A more recent public survey was conducted in Japan to clarify preferences among representative 40-79 year-olds for place of death and EOL care.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is also a discrepancy between what patients report as their preferred place of death (most often home) and actual place of death (Beccaro et al 2006;Bruera et al 2003;Burge et al 2003;Foreman et al 2006;gilbar and steiner 1996;karlsen and Addington-Hall 1998;Mcwhinney et al 1995;Heyland et al 2000;Pritchard et al 1998). People who die in institutions such as acute care facilities have unmet needs for symptom control, physician communication, emotional support and respectful treatment compared with those receiving patientcentred palliative care services at home (Teno et al 2004).…”
Section: Résumémentioning
confidence: 99%